Color outside the lines : stories about love - Mandanna, Sangu; Ahmed, Samira; Chapman, Elsie; Gibaldi, Lauren; Kang, Lydia; Keil, Michelle Ruiz; Lee, Lori M.; Mandanna, Sangu; McKinney, L. L. (Leatrice L.); McLemore, Anna-Marie; Paige, Danielle (Novelist); Riazi, Karuna; et al. (Soho Teen, 2019)
An anthology of short stories exploring interracial and other relationships, in which differences are front and center, but may or may not matter.